LAHIRNYA PERBANKAN SYARI’AH DI INDONESIA - Mulyani, Rita (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2019)
With the development of increasingly advanced times, the bank continues to make new innovations so that at this time the bank is no longer just an institution that functions to collect and distribute funds, but at the same time also as an intermediary in the payment traffic. However, the Muslim community strives to realize banking based on sharia principles. For this reason, several Muslim countries have slowly begun to establish Islamic Banks. The development of Islamic banking is quite significant in several countries, but of the many countries, Indonesia actually has a different side. The difference lies in the term used to refer to a non-conventional bank. While other countries commonly refer to it as an Islamic Bank, in Indonesia it is actually called the Sharia Banking because the idea of ​​the Islamic Bank is alleged to have contained political and SARA elements. With high stretches owned by several Muslim countries to establish shari'ah banking, Indonesia as the country with the largest Muslim population in the world established the first sharia banking under the name Bank Muamalat Indonesia (BMI) which was officially operated in 1992. From year to year, Sharia banking growth is very fast. Keywords : Banking, Sharia Banking,Indonesia. Abstrak Dengan perkembangan zaman yang semakin maju, bank terus melakukan inovasi baru sehingga pada saat ini bank tidak lagi hanya sekedar lembaga yang berfungsi menghimpun dan menyalurkan dana saja, namun sekaligus juga sebagai intermediasi dalam lalu lintas pembayaran. Namun, komunitas Muslim berusaha untuk mewujudkan perbankan berdasarkan prinsip syariah. Atas dasar alasan inilah, beberapa negara muslim perlahan mulai mendirikan Bank Islam. Perkembangan perbankan Islam cukup signifikan terjadi di beberapa negara, tetapi dari sekian banyak negara, Indonesia justru memiliki sisi yang berbeda. Perbedaan tersebut terletak pada istilah yang dipakai untuk menyebut bank yang nonkonvensional.Di saat negara-negara lain lazim menyebutnya sebagai Bank Islam, di Indonesia justrumenyebutnya Bank Syari’ah karena istilah Bank Islam diduga mengandung unsur politik dan SARA.Dengan geliat tinggi yang dimiliki oleh beberapa negara muslim untuk mendirikan perbankan syari’ah, Indonesia sebagai negara dengan populasi muslim terbesar di dunia mendirikan perbankan syariah pertama dengan nama Bank Muamalat Indonesia (BMI) yang secara resmi beroperasi pada tahun 1992.Dari tahun ke tahun, pertumbuhan perbankan syari’ah sangatcepat. Kata Kunci : Perbankan, Perbankan Syariah, Indonesia.